2019
DOI: 10.5435/jaaos-d-18-00655
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Posterior Capsular Dehiscence After Posterior Approach Total Hip Arthroplasty

Abstract: Introduction: To our knowledge, no previous study has evaluated the use of MRI to diagnose posterior capsule dehiscence after posterior approach total hip arthroplasty (THA) with capsular repair and its association with postoperative posterior hip dislocation. Methods: A retrospective chart review of patients who underwent posterior approach THA with capsulotomy repair was performed. Patients were identified who subsequently underwent MRI, and these stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Allegra et al (15) found intact capsular structure on MRI one year after surgery in 15 of 32 (48%) patients undergoing posterior capsule repair. Moon et al(6) reported a 18% failure rate of capsular repair due to insu cient structure and repair under tension, observed a signi cant correlation between suture failure and dislocation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Allegra et al (15) found intact capsular structure on MRI one year after surgery in 15 of 32 (48%) patients undergoing posterior capsule repair. Moon et al(6) reported a 18% failure rate of capsular repair due to insu cient structure and repair under tension, observed a signi cant correlation between suture failure and dislocation.…”
Section: Discussionmentioning
confidence: 98%
“…The sample size was calculated based on the preliminary results of the previous studies. The successful rate of mesh group (treated with mesh reconstruction) was 90% in the preliminary experiment, and the successful rate of conventional group (treated with conventional capsular repair technique) was 65% (15). We selected con dence (1-β) = 0.80, signi cant level α=0.025 (unilateral), and superiority margin δ=0.025.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers believe that the capsule plays an important role in the biomechanical stability of the hip [ 2 , 11 14 ]. However, repair failure may occur due to limited capsular tissue, and approximately half of hips fail to achieve adequate stability due to capsular dehiscence [ 6 , 15 , 16 ]. Larger hip offset, longer repair distance and earlier exercise increased the incidence of repair failure.…”
Section: Introductionmentioning
confidence: 99%